A new beaked whale (Cetacea, Odontoceti) from the Late Miocene of Patagonia, Argentina - Buono, Mónica Romina (2013)
A new genus and species of Ziphiidae, Notoziphius bruneti, gen. et sp. nov., from the late Miocene of Patagonia, is described on the basis of a well-preserved skull and partial left and right dentaries. It can be diagnosed by large, triangular, and markedly asymmetric nasals that strongly point anteroventrally, the ascending process of the maxilla not expanded posteriorly, supraoccipital strongly sloped posteroventrally; elliptical fossa on the nasal process of the premaxilla, small and anterolaterally directed premaxillary crest, and the presence of well-defined alveoli in the maxilla. A phylogenetic analysis including 25 ziphiid genera and 31 characters shows Notoziphius as nested within Ziphiidae in a basal clade with Aporotus, Beneziphius, Messapicetus, and Ziphirostrum. This clade is diagnosed by medial fusion of the premaxillae that closes the mesorostral groove, lateral margin of prenarial basin formed by a thick strip of maxilla, premaxillary crest anterolaterally directed, and reduced contact between nasal and premaxillary crest. The presence of Notoziphius in the Miocene of Patagonia increases our knowledge of ziphiid diversity in South America. Notoziphius bruneti and other Miocene records of ziphiids reinforce the idea that during the Miocene ziphiids were widely distributed and diverse.